Human enhancement drugs and new(?) research directions - van de Ven, K.; Dunn, M.; Mulrooney, K. (Performance Enhancement & Health, 2020)
In February 2020 the Human Enhancement Drugs Network (HEDN; www.HumanEnhancmentDrugs.com) organised a symposium entitled "Human Enhancement Drugs and New Research Directions". Human enhancement drugs (HEDs) includes "substances that are used as functional aids - their predominant purpose is not primarily immediate gratification or pleasure (in contrast to psychoactive drugs) but are rather often utilized in the pursuit of excellence, the attempt to surpass one`s natural potential, and/or the attempt to retain, regain or recover a quality, skill or standard. In short, this may be expressed as "better than well"" (van de Ven, Mulrooney, & McVeigh, 2019, p. 3). The aim of the symposium was to bring together a broad spectrum of scholarly insights and research expertise from various disciplines to examine key (inter)national issues in the field of enhancement drugs. Its purpose was to facilitate debates on our understanding of the cultural and societal contexts of HED use and supply, as well as the critical analysis of (the consequences of) policy implementation. Approximately 30 people attended the symposium (in person and via Zoom) including academics, anti-doping officials, drugs/health/implementation science researchers, chemists, a retired athlete, a lawyer, and needle and syringe program (NSP) staff. At the end of the symposium, attendees were asked to submit what they believed to be the three most important issues in this field; i.e. what are some of the key problems they would like to see addressed and where would like more research to be focused? In this editorial, we (the organisers of the event and board members of HEDN) will reflect on the priorities that have been raised during this symposium. We have purposely added the question mark behind the word "new" in our title, because as we will show some of the raised priorities are not necessarily new but have remained important long-standing issues.